A descriptive analysis of notifiable gastrointestinal illness in the Northwest Territories, Canada, 1991–2008. Issue 4 (2nd July 2012) - Pardhan-Ali, Aliya; Wilson, Jeff; Edge, Victoria L; Furgal, Chris; Reid-Smith, Richard; Santos, Maria; McEwen, Scott A
Abstract : Objectives: To describe the major characteristics of reported notifiable gastrointestinal illness (NGI) data in the Northwest Territories (NWT) from January 1991 through December 2008. Design: Descriptive analysis of 708 reported cases of NGI extracted from the Northwest Territories Communicable Disease Registry (NWT CDR). Setting: Primary, secondary and tertiary health care centres across all 33 communities of the NWT. Population: NWT residents of all ages with confirmed NGI reported to the NWT CDR from January 1991 through December 2008. Main outcome measure: Laboratory-confirmed NGI, with a particular emphasis on campylobacteriosis, giardiasis and salmonellosis. Results: Campylobacteriosis, giardiasis and salmonellosis were the most commonly identified types of NGI in the territory. Seasonal peaks for all three diseases were observed in late summer to autumn (p<0.01). Higher rates of NGI (all 15 diseases/infections) were found in the 0–9-year age group and in men (p<0.01). Similarly, rates of giardiasis were higher in the 0–9-year age group and in men (p<0.02). A disproportionate burden of salmonellosis was found in people aged 60 years and older and in women (p<0.02). Although not significant, the incidence of campylobacteriosis was greater in the 20–29-years age group and in men (p<0.07). The health authority with the highest incidence of NGI was Yellowknife (p<0.01), while for salmonellosis and campylobacteriosis, it was Tlicho (p<0.01) and for giardiasis, the Sahtu region (p<0.01). Overall, disease rates were higher in urban areas (p<0.01). Contaminated eggs, poultry and untreated water were believed by health practitioners to be important sources of infection in cases of salmonellosis, campylobacteriosis and giardiasis, respectively. Conclusions: The general patterns of these findings suggest that environmental and behavioural risk factors played key roles in infection. Further research into potential individual and community-level risk factors is warranted.